Neutrophil and monocyte responses to downhill running: Intracellular contents of MPO, IL‐6, IL‐10, pstat3, and SOCS3. Issue 6 (9th June 2015) - van de Vyver, M.; Engelbrecht, L.; Smith, C.; Myburgh, K. H.
Abstract : High‐intensity exercise results in immune activation. This study determined whether (a) there is concordance between serum MPO and neutrophil and/or monocyte intracellular MPO content; (b) peripheral blood mononuclear cells respond to inflammatory interleukins (ILs) by increasing intracellular signaling. Healthy male ( n  = 12) volunteers participated in high‐intensity running (12 × 5 min, 10% decline, 15 km/h). Blood sample (pre, post, 4 h) analyses included serum concentrations of IL‐1β, IL‐1ra, IL‐4, IL‐6, IL‐8, IL‐10, matrix metalloprotease‐9 (MMP‐9) and creatine kinase (CK). Intracellular IL‐6, IL‐10, MPO and STAT3/SOCS3 signaling were assessed in mononuclear cells. CK (1573 ± 756 u/L), MMP‐9 (101 ± 27 ng/mL), neutrophil (9.89 ± 0.76 × 10 9 cells/L) and monocyte counts (1 ± 0.08 × 10 9 cells/L) increased at 4 h. At 4 h serum (7.1 ± 1.3 ng/mL) and monocyte MPO (1.7‐fold) increased, whereas neutrophil MPO decreased (0.8‐fold). Intracellular monocyte IL‐10 and IL‐6 decreased by 15% and 20–30%, respectively, coinciding with elevations in serum IL‐10 of 14.5 ± 4.7 pg/mL and IL‐6 of 5.4 ± 2.9 pg/mL, suggesting immune cell cytokine release in response to exercise. Intracellular PBMC p‐STAT3 to total STAT3 ratio increased from pre to 4 h. Circulating monocytes are responsive to increased serum IL‐6 suggesting a negative feedback loop via STAT3 signaling.